2016
DOI: 10.1002/pbc.26221
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of semen parameters in a young cohort of cancer patients

Abstract: Our data support that sperm banking pubertal males prior to the initiation of therapy is feasible. While there were differences in quality of semen parameters across age and diagnostic groups, most males, regardless of age or diagnosis, had adequate specimens for cryopreservation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 28 publications
0
32
0
Order By: Relevance
“…It has been suggested that as many as two-thirds of cancer patients have impaired fertility at baseline (van Casteren et al, 2010), but studies have reported heterogeneous findings as to whether and how specific types of malignancy are linked to diminished semen parameters (Auger et al, 2016;Caponecchia et al, 2016;Paoli et al, 2016;DiNofia et al, 2017;MacKenna et al, 2017). It has been suggested that as many as two-thirds of cancer patients have impaired fertility at baseline (van Casteren et al, 2010), but studies have reported heterogeneous findings as to whether and how specific types of malignancy are linked to diminished semen parameters (Auger et al, 2016;Caponecchia et al, 2016;Paoli et al, 2016;DiNofia et al, 2017;MacKenna et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that as many as two-thirds of cancer patients have impaired fertility at baseline (van Casteren et al, 2010), but studies have reported heterogeneous findings as to whether and how specific types of malignancy are linked to diminished semen parameters (Auger et al, 2016;Caponecchia et al, 2016;Paoli et al, 2016;DiNofia et al, 2017;MacKenna et al, 2017). It has been suggested that as many as two-thirds of cancer patients have impaired fertility at baseline (van Casteren et al, 2010), but studies have reported heterogeneous findings as to whether and how specific types of malignancy are linked to diminished semen parameters (Auger et al, 2016;Caponecchia et al, 2016;Paoli et al, 2016;DiNofia et al, 2017;MacKenna et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Electroejaculation must be performed under general anesthesia. 40 Despite this recommendation, an inadequate duration of time between the diagnosis and initiation of therapy often is perceived as a barrier to sperm cryopreservation. 5 In a retrospective cohort study of semen parameters for a large cohort of adolescents and young adults with cancer, approximately 84.0% of patients who provided a semen specimen after the initiation of treatment were azoospermic, compared with only 16.9% in untreated patients.…”
Section: Sperm Cryopreservationmentioning
confidence: 99%
“…40 Despite this recommendation, an inadequate duration of time between the diagnosis and initiation of therapy often is perceived as a barrier to sperm cryopreservation. 38,40,45,46 However, an adequate semen specimen can be obtained in adolescents as young as 11 years of age. Several centers have been successful with sperm cryopreservation in >80% of adolescents and young adults prior to the initiation of therapy.…”
Section: Sperm Cryopreservationmentioning
confidence: 99%
See 2 more Smart Citations